Genome-wide identification of Solanum tuberosum L. AAAP gene family and its response to abiotic stress - Zhichang Gao; Xinrui Zhao; Yanqun Wang; Xiaotian Chen; Lei Wang; Xiaojing Liu; Jianghui Cui (PLoS ONE, 2025)
The amino acid/auxin permease (AAAP) protein is an amino acid transporter involved in many biological processes in plants, especially in plant responses to abiotic stress. This study systematically identified potato StAAAP gene family, revealed its characteristics, and analyzed its functions in potato resistance to abiotic stress. Furthermore, its gene structure, chromosome distribution, cis-acting elements, conserved protein moieties, and collinearity between species were analyzed. The expression pattern of StAAAP in potato plants under abiotic stress was analyzed using RNA-seq data downloaded from the National Center for Biotechnology Information (NCBI), and the gene expression pattern was verified using qRT-PCR. A total of 56 members of the StAAAP gene family were identified in potato and were distributed across 12 chromosomes. Based on their phylogenetic characteristics, they were divided into eight subfamilies: ATLa, ATLb, AAP, ANT, AUX, GAT, LHT, and ProT. The gene structure and conserved motifs of members of the same subfamily are essentially the same, and the AAAP gene family members are mostly distributed in the plasma membrane. Potato StAAAP family members contain a large number of cis-acting elements related to the stress response. Collinearity analysis revealed a large number of homologous gene pairs in the potato, tomato, pepper, and tobacco AAAP families. Expression analysis revealed that StAAAP family members were highly expressed under drought and salt stress conditions, and the expression of the same gene was different in different family members. The genes StAAAP4, StAAAP24, StAAAP29, StAAAP40, and StAAAP46 may play key roles in the abiotic stress response of potatoes. StAAAP genes play an important role in the growth, development, and abiotic stress responses of potato plants.